Emily Brontë and the Enthusiastic Tradition - Mason, Emma (Romanticism on the Net, 2002)
AbstractThis essay places Emily Brontë's poetry within a tradition of eighteenth-century discourses on enthusiasm of both a poetical and religious nature. The question of where Brontë's fervent writing style, most often associated with her fiery novel Wuthering Heights, originated has long been debated, and it is suggested here that one available answer is enthusiasm. Two sources of enthusiasm pertinent to Brontë are explored: Methodism, with its dislike of doctrine and pantheistic emphasis on nature; and eighteenth-century poetics, as defined through figures like John Dennis and Edward Young. Religious and poetical enthusiasm are necessarily merged for Brontë, both infused by a kind of spiritual sublimity and dependence on the idea of transport she employed within her verse. Recognizing this allows the reader to historicize this often cryptic poet and thus rescue her from more arguably tenuous claims which deem her a mystic, a Shelleyan heretic, a writer repressed by Christianity, a victim of a tragic romance or simply a very angry woman. By instead locating her within an enthusiastic literary tradition, Brontë may be seen not only as a woman writer aware of her religious environment, but as a Romantic whose poetry accords as much with the sentiment of Night Thoughts as Mont Blanc.